Does distance matter in deposit supply? A bank-level study - Ari Hyytinen; Otto Toivanen (The Research Institute of the Finnish Economy (ETLA), 2002)
We study empirically the determinants of deposit supply using bank level data from local Finnish cooperative banks. Of special interest is the effect of bank branch density on deposit supply. Our main finding is that holding other things constant, the denser the branch network, the lower the deposit rate. We also find that the effect of the branch network decreases over time. Our evidence thus suggests that quite like in the US small business lending (Petersen and Rajan 2001), distance matters in deposit supply, but less than before. – banking ; deposit supply ; branch network – – Työpaperissa analysoidaan empiirisesti talletusten tarjontaa määrääviä tekijöitä käyttämällä pankkitason aineistoa. Tarkastelemme erityisesti sitä, kuinka konttoriverkoston tiheys vaikuttaa talletusten tarjontaan. Keskeinen tulos on, että kun monien muiden tekijöiden vaikutusta kontrolloidaan, tiheä konttoriverkosto näyttää johtavan alhaisempaan talletuksille maksettavaan korkoon. Konttoriverkoston vaikutus on kuitenkin heikentymässä. Tuloksemme ovat yhdenmukaisia Petersenin ja Rajanin (2001) yhdysvaltalaisella luottoaineistolla saamien tulosten kanssa: (fyysisellä) etäisyydellä on merkitystä edelleen, mutta sen merkitys on vähenemässä.
Keywords: G21; G30; L15; 330; Banking-Schule; Einlagengeschäft; Branche